Roles of private healthcare facilities in post-test counselling and referral for HIV services during antenatal care in South-West Nigeria - Henry Osaro Aisagbonhi; Yejide Olukemi Oseni; Mayowa Omolabake Odofin; Ezioma Anne Chukwu; Ukamaka Gladys Okafor; Ifeoluwa Silvanus Abiodun; Treasure Wariboko Obiajulu Okoye; Oluwadamilola Aminat Sadare; Eugenia Onwuchuluba Ebele; Esther Ametor Ajakaiye; Azeezat Abimbola Oyewande (Discover Health Systems)
Abstract Background In Nigeria, an estimated 22% of children acquired HIV from mother-to-child transmission during delivery in 2019 while many pregnant women seek care through private-sector health facilities. This study evaluated the role private-sector health facilities play in post-test counselling and referral for HIV services among pregnant women. Methods Using a structured questionnaire, a cross-sectional design, facility-based study (with protocol ID no. OOUTH/HREC/605/2023AP), was conducted among 180 healthcare providers in traditional birth attendant facilities, maternity homes, and private hospitals across three Nigerian states. Data were analyzed with descriptive (frequencies, percentages, means, SDs) and inferential statistics (Chi-square, ANOVA, regression) and p-value set at ≤ 0.05. Results Most respondents were female (82.2%), aged 20–30 years (30.0%), auxiliary nurses/midwives (61.7%) and traditional birth attendants (43.3%). Over half (56.7%) had training on antenatal care (ANC) for HIV-positive pregnant women, and 94.4% of respondents’ facilities screened for HIV. Of those who provided screening, 82.9% had encountered positive HIV results, and 53.5% provided ANC for HIV-positive clients. Services included safe childbirth (94.5%), post-test counselling (91.2%), prevention of mother-to-child transmission (85.7%), antiretroviral therapy (56.0%), and infant HIV testing (35.2%). Facilities without ANC services (46.5%) immediately referred patients to other health facilities. Most facilities with screening services had written counselling procedures (64.7%), disclosed HIV status immediately (71.8%), and further supported patients with referral services (93.5%). State of practice, type of facility, and training in ANC services were associated with the provision of ANC services for HIV-positive pregnant women (p< 0.05) while the age of respondents, gender and level of education did not (p> 0.05). Conclusion Private-sector facilities play a crucial role in ANC for HIV-positive pregnant women. Still, gaps in antiretroviral therapy and infant HIV testing highlight the need for targeted interventions to optimize care.